Effect of the particle size of PZT on the microstructure and the piezoelectric properties of 0-3 PZT/polymer composites - Rujijanagul G. (2014)
Effect of particle size of lead zirconate titanate (PZT) on the microstructure and the piezoelectric properties of 0-3 PZT/polymer composites was investigated. The PZT powders were prepared by conventional solid-state reaction and the size of the particles was classified by sieving method to obtain similar physical properties of the powders. X-ray diffraction analysis (XRD) and scanning electron microscopy (SEM) were used to study the microstructure of the ceramics. More homogeneity of the particle distribution was observed in the composites with smaller PZT particles. The dielectric constant was also found to be higher in composites containing coarse particles and higher volumetric percentages of the PZT phase.